2018
DOI: 10.2196/jmir.9390
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Education and Support in a Virtual Environment: A Secondary Analysis of Synchronously Exchanged Social Interaction and Support

Abstract: BackgroundVirtual environments (VEs) facilitate interaction and support among individuals with chronic illness, yet the characteristics of these VE interactions remain unknown.ObjectiveThe objective of this study was to describe social interaction and support among individuals with type 2 diabetes (T2D) who interacted in a VE.MethodsData included VE-mediated synchronous conversations and text-chat and asynchronous emails and discussion board posts from a study that facilitated interaction among individuals wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 55 publications
(72 reference statements)
0
32
1
Order By: Relevance
“…80 Virtual environments can enable the feeling of being virtually present (presence) or virtually co-present (co-presence) with others through capabilities like synchronous voice communication and avatar representation of self. 89 Co-presence in virtual environments is associated with higher levels of engagement and enjoyment in learning, as opposed to solely playing against a computer. 90 Anonymity and co-presence foster self-disclosure.…”
Section: A Proposed Stepwise Multi-construct Framework Towards Trustwmentioning
confidence: 99%
See 3 more Smart Citations
“…80 Virtual environments can enable the feeling of being virtually present (presence) or virtually co-present (co-presence) with others through capabilities like synchronous voice communication and avatar representation of self. 89 Co-presence in virtual environments is associated with higher levels of engagement and enjoyment in learning, as opposed to solely playing against a computer. 90 Anonymity and co-presence foster self-disclosure.…”
Section: A Proposed Stepwise Multi-construct Framework Towards Trustwmentioning
confidence: 99%
“…81 Preliminary work conducted in a one group feasibility pilot study (SLIDES -Second Life Impacts Diabetes Education and Support) informed the development of LIVE and demonstrated that among a small pilot group of patients with diabetes, perceived support increased, and some participants formed longer term supportive relationships with each other and the health professionals. 80,89 The analysis of the qualitative data collected in SLIDES 89 highlights the potential value of virtual environments in addressing trust among those living with chronic conditions, including diabetes, heart disease, and HIV. Lewinski found that the ties between many participants evolved and became stronger (i.e., closer) and that the personal nature of the narratives shared regarding living with diabetes also increased over time.…”
Section: Ehealth Exemplar 1: Virtual Environment For Diabetes Self-mamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, they provide the added benefit of allowing participating members of the diabetes community to interact with each other, which has beneficial effects on both metabolic and psychosocial outcomes. [21][22][23] However, there may be some attrition in using these services over time. 21,22 Diabetes App Use…”
Section: Virtual Education and Medical Visitsmentioning
confidence: 99%